Language Competence as Part of Language Education: Structure, Content (Eurasian Journal of Learning and Academic Teaching, 2023)
The core of language education lies in one’s ability to comprehend and produce language effectively. The skill to communicate proficiently using language in varying settings and with diverse individuals is known as communicative competence. In order to attain this goal, language learners should enhance their knowledge on various language aspects such as grammar, vocabulary, pronunciation, and discourse, along with improving their ability to effectively communicate. This article explores how language competence contributes to the development of language through analyzing its structure and content